2019
DOI: 10.4236/fns.2019.102011
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidine-3-O-Galactoside Enriched <i>Aronia melanocarpa</i> Extract Inhibits Adipogenesis and Lipogenesis via Down-Regulation of Adipogenic Transcription Factors and Their Target Genes in 3T3-L1 Cells

Abstract: Aronia melamocarpa (AM) is a rich source of anthocyanins, which are known to help prevent obesity. The cyanidine-3-O-galactoside enriched AM extract (AM-Ex) containing more cyanidine-3-O-galactoside than conventional AM extract was recently developed. The objective of this study was to examine the effect of AM-Ex on adipogenesis and its action mechanisms in vitro using 3T3-L1 adipocytes. To examine the anti-obesity effect of AM-Ex, 3T3-L1 cells were induced adipocyte differentiation and incubated with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…When extracted with the new extraction method, the content of cyanidin-3- O -galactoside was 2408 mg/100 g, which was about 2.4 times higher than that of conventional methods. Our in vitro studies using 3T3-L1 cells showed that this AM-Ex inhibited adipogenesis [26]. This study was conducted to investigate the anti-obesity properties of cyanidin-3- O -galactoside-enriched AM-Ex in an in vivo system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When extracted with the new extraction method, the content of cyanidin-3- O -galactoside was 2408 mg/100 g, which was about 2.4 times higher than that of conventional methods. Our in vitro studies using 3T3-L1 cells showed that this AM-Ex inhibited adipogenesis [26]. This study was conducted to investigate the anti-obesity properties of cyanidin-3- O -galactoside-enriched AM-Ex in an in vivo system.…”
Section: Discussionmentioning
confidence: 99%
“…AM-Ex was prepared by Wellfine Co., Ltd (Hoengseong, Gangwon, Korea). according to the method described previously [26]. In brief, the freeze-dried powder of Aronia melanocarpa Nero fruits was extracted with 70% ethanol by adding 100 g of the dried powder to 2 L of 70% ethanol using a high pressure homogenizer (Micronox, Seongnam, Korea) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 8 days of differentiation and treatment with COME, the total RNA in the cells was extracted, reverse transcribed, and real-time RT-PCR was conducted using a QuantiNova SYBR Green PCR kit (Qiagen) and a Rotor-gene 3000 PCR (Corbett Research, Mortlake, Australia), as reported elsewhere [ 27 ]. Table 1 lists the sequences of the PCR primers utilized in this study.…”
Section: Methodsmentioning
confidence: 99%